ACUTE TOXICITY TEST OF ETANOL EXTRACT FROM MANGOSTEEN PERICARP (Garcinia mangostana L. ) AGAINST ARTEMIA SALINA LEACH LARVAE USING BRINE SHRIMP LETHALITY TEST (BST) - Fatimawali, Fatimawali (PHARMACON, 2013)
The aim of this research is to determine acute toxicity potency of mangosteen pericarp extract using Brine Shrimp Lethality Test (BST). This research was an experimental research using Post Test Only Control Group Design, using 250 larvaes as test subject which were divided into 5 groups. Each group contains 10 larvaes and each group was done by 5 replications. The test componen was mangosteen pericarp extract that given through the media which contains larvae as the animal test. The extract final concentration in media which contains larvae were 1000, 500, 200, 100 and 0 ppm as negative control. The result is against larvae that died 24 hours after component test was given. Through the data, LC 50 value of etanol extract of mangosteen rind was analyzed. The result shows that mangosteen rind extract on the media could kill larvae of Artemia salina. Prohibit analyzes shows that mangosteen extract LC50 value of mangosteen pericarp extract was 418 ppm. So the administering of rind extract of mangosteen (Garcinia mangostana L.) had acute toxicity potential against Artemia salina Leach larvae according to BST method. Â Keywords : Garcinia mangostana L. pericarp, brine shrimp lethality test, acute toxicity